Shear and compression behaviour of crushed mudrocks in Malaysia - Che Mohd Rosley, Ili Syazwani (2019)
Mudrocks is a type of rock that tends to deteriorate upon exposure to water. Studies have found mudrocks to be in low to medium durability in which its shear strength and compressibility were easily influenced by its resistance towards wetting and drying. However, in Malaysia, it is difficult to avoid mudrocks from exposure to water due to the tropical climate. When mudrocks were encountered on construction sites, they were often been excavated however, it is not a sustainable solution. Thus research on shear and compression behaviour of crushed mudrocks with detailed explanations on morphological changes that relate with mineralogical and chemical composition is required before suitable stabilisation or any advance solutions on working out crushed mudrocks as geotechnical material could be carried out. Hence this research implied direct shear tests, XRD, XRF and VPSEM to evaluate the shear and compression behaviour of crushed mudrocks in Malaysia. This study was conducted onto mudrocks in Malaysia from Putrajaya, Semanggol (Perak) and Durian Tunggal (Melaka). The materials were named as CM1, CM2, and CM3 respectively. These crushed mudrocks predominantly contained of swelling clays where CM1 contained 38.2%, CM2 contained 35.1% and CM3 contained 58% of swelling clays respectively. Three types of slaking tests were carried out; jar slake test, slake durability test, and slaking immersion test. Based on the results, CM2 was the most durable, followed by CM1 and lastly CM3. This pattern of sequence agrees with swelling clay minerals contents but went inversely with total mica contents in which CM2 has the highest with 34.7%, followed by CM1 with 29.4% and lastly CM3 with 25%. Shear and compression behaviour of crushed mudrocks were investigated at various compaction degree, various initial moisture content, and various terms of immersion in which the tests were accompanied with staged-loading process using direct shear box test. Higher compaction degrees caused crushed mudrocks to exhibit highest peak shear strength in which decrease of subsequent 5% compaction degrees had caused 11% to 12% peak shear strength reduction and 2% compression to take place. Due to increment of initial moisture content from natural to optimum, peak shear strength of crushed mudrocks increased by 4.4% to 6.9% with reduced brittleness and about 0.6% to 1.2% compression took place since early loading stage. Upon immersions, direct shear tests revealed that all crushed mudrocks failed in brittle deformation when without immersion. Short term immersion had intensified crushed mudrocks brittle behaviour with peak shear strength reduction of 15% for CM1 and CM2, and 42% for CM3. Long term immersion, on the other hand had caused only 3% strength reduction with fully plastic straining behaviour after failure. In addition, short term immersion caused immediate compression of about 3% to crushed mudrocks while long term immersion caused CM1 and CM2 to show progressively reduced compression, and CM3 to show progressive compression along stagedloading process.VPSEM images shown that vigorous micro activities that took place during short term immersion had led to strength reduction and high compressibility of mudrocks while long term immersion had enabled prolonged micro-activities hence resulted into higher peak shear strength than that of recorded by short term immersion. As a result, micro flaws; micro holes, micro fracture and micro cracks were seen from VPSEM images of mudrocks after short term immersion. The micro flaws had caused mudrocks to experience strength reduction and high compression. However the micro flaws were seen resealed after long term immersion as prolonged micro activities had promoted healing to the flaws. Interestingly, these micro activities were able to occur due to presence of swelling clay minerals which seem to have increased aggregate’s ability to absorb water and to weave with each other. This study hence found that mudrocks are not only sensitive to moisture changes but to sudden moisture changes as pictured through short term immersion while prewetting effect through long term immersion had reduced mudrocks sensitivity towards moisture changes throughout staged-loading.